Intermediate to Long-Term Follow-up of the Salto Talaris Fixed-Bearing Total Ankle Prosthesis. Issue 3 (June 2023) - Vesely, Bryanna D.; King, Matthew A.; Scott, Aaron T.
Background: Total ankle arthroplasty (TAA) remains a viable option for recalcitrant, end-stage ankle arthritis. Among the various Food and Drug Administration (FDA)-approved prosthetic options is the fixed-bearing Salto Talaris implant. The aim of the present study was to evaluate the intermediate to long-term clinical outcomes and radiographic complications following implantation of the Salto Talaris TAA. Methods: Nineteen Salto Talaris total ankle implants were included in the present retrospective study. Medical records were reviewed to determine pre- and postoperative visual analog scale (VAS) pain scores, and both medical records and radiographs were utilized to assess for complications. Telephone interviews were then conducted to assess for overall patient satisfaction. Results: At a mean follow of 6.9 years (range, 3.5-12 years), there was a 21% complication rate according to the classification system described by Glazebrook et al. The reoperation rate was low at 10.5%, and there was 100% survivorship of the total ankle implant. The average pain decreased from 9.1 (range, 7-10) preoperatively to 2.6 (range, 0-10) postoperatively. Patients reported a 95% satisfaction rate, and 16% of patients reported using a brace postoperatively. Conclusion: The Salto Talaris arthroplasty was associated with low complication and reoperation rates, and a high survivorship at intermediate to long-term follow-up. Levels of Evidence: 4